Optimization analysis of external prestressing reinforcement scheme for concrete curved girder bridge. (January 2019) - Li, Hongbin; Zhang, Lianrui; Zhong, Tieyi; Wang, Jiawei
Abstract: In this paper, the external prestressing method is used to reinforce a prestressed concrete curved girder bridge. The calculation and analysis model of external prestressing reinforcement is established. The alignment of external prestressing tendons and the tension control stress are studied. The reasonable alignment of external prestressing tendons and the parameters of tension control stress are given. The results show that when two steering blocks are set at one-fourth span and three-quarters span to control the alignment and the prestress value outside the curved girder bridge is 25%-35% larger than that inside the bridge, not only the bearing capacity and stiffness requirements can be met, but also the torque produced by the main girder under the external load can be effectively reduced.